Method for producing aluminum nitride powder, aluminum nitride powder and package
By using aluminum nitride particles below 3 μm as diluent in the direct nitriding method, and carrying out combustion synthesis reaction and light pulverization, the problems of poor moldability and low thermal conductivity of aluminum nitride powder are solved, and efficient and low-cost aluminum nitride powder manufacturing is achieved.
Patent Information
- Application Number
- CN202180012077.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-06
- Filing Date
- 2021-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-01-22
AI Technical Summary
When the current direct nitriding method is used to produce aluminum nitride powder, coarse particles are easily generated, resulting in increased impurities during crushing, reduced thermal conductivity, and poor moldability.
Under specific conditions, aluminum nitride particles of 3 μm or less are used as diluents, and aluminum nitride is produced by combustion synthesis reaction, followed by light pulverization to obtain particles of 20 μm or less.
The bulk state of aluminum nitride is easily refined, the formation of oxide layers is reduced, the thermal conductivity and electrical characteristics of aluminum nitride powder are improved, and it has high efficiency and high moldability during calcination.
Abstract
Description
Technical Field
[0001] The present invention relates to an industrial process for producing aluminum nitride powder which can be used for sintered body applications. Background Art
[0002] Aluminum nitride has excellent properties such as high electrical insulation, high plasma resistance, and high thermal conductivity, and is therefore widely used in insulating heat dissipation substrates, semiconductor manufacturing equipment materials, etc. These are produced by adding a sintering aid to aluminum nitride powder as needed and using an organic binder for molding, and then degreasing and sintering under normal pressure or pressure. When yttrium oxide, a representative sintering aid, is used, it captures impurity oxygen in aluminum nitride to achieve high thermal conductivity.
[0003] As general industrial production methods for aluminum nitride powder, there are known a reduction nitridation method in which a mixed powder of aluminum oxide powder and carbon powder is heated to a high temperature in nitrogen gas, and a direct nitridation method in which metallic aluminum and nitrogen gas are reacted at a high temperature.
[0004] Among them, the method of direct nitridation, which is implemented industrially, is a method of performing a nitridation reaction of metallic aluminum by external heating. The obtained aluminum nitride powder contains coarse particles that are fused by the heat during the reaction, and therefore, it is usually subjected to a pulverization process. Therefore, the pulverization process easily leads to an increase in metal impurities and surface oxygen, and when a sintered body is formed, lattice defects are generated due to these impurities, which leads to a decrease in thermal conductivity. In addition, the shape of the particles obtained by pulverization is amorphous, and there is a concern that the moldability will deteriorate.
[0005] On the other hand, the aluminum nitride powder obtained by the reduction nitridation method has an average particle size of about 1 μm and fewer coarse particles than the aluminum nitride powder obtained by the direct nitridation method. The particle shape is also close to spherical and has high purity. Therefore, it has excellent formability and sinterability, and it is easy to obtain high thermal conductivity when forming a sintered body.
[0006] However, since the reduction nitridation method requires mixing carbon and aluminum oxide and decarburizing the residual carbon, the direct nitridation method is more advantageous in terms of raw material cost and energy cost, and can also be produced continuously in industry. Therefore, it is expected that the direct nitridation method can also produce aluminum nitride equivalent to the reduction nitridation method.
[0007] The combustion synthesis method is known as one of the direct nitriding methods. In this method, a part of a raw material powder layer formed of metal aluminum is ignited in a nitrogen atmosphere, and the reaction heat generated by the subsequent reaction is transferred to the above powder layer, thereby promoting the nitriding reaction to synthesize aluminum nitride.
[0008] Al+1 / 2N 2 →AlN-ΔH 0
[0009] In the reaction formula, 〔-ΔH 0 〕=320KJ / mol, and its heat release is the driving force of the combustion synthesis reaction.
[0010] As a method for producing aluminum nitride by the combustion synthesis method of metallic aluminum, for example, Japanese Patent Publication No. 7-309611 (Patent Document 1) and Japanese Patent Publication No. 2000-16805 (Patent Document 2) are known. These patent documents disclose that aluminum nitride powder is added as a diluent together with metallic aluminum to perform the combustion synthesis method.
[0011] It should be noted that Japanese Patent Gazette No. 7-81909 (Patent Document 3) discloses a method for producing silicon nitride by a combustion synthesis method, in which, in order to prevent the silicon nitride to be synthesized from being obtained in the form of a solid block, it is recorded that the volume density of the mixed powder formed by the silicon nitride powder as a diluent (aggregate) and the metallic silicon powder is adjusted in a manner to be reduced.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 7-309611
[0015] Patent Document 2: Japanese Patent Application Publication No. 2000-016805
[0016] Patent Document 3: Japanese Patent Application Laid-Open No. 7-081909 Summary of the invention
[0017] Problem that the invention aims to solve
[0018] However, the aluminum nitride obtained by the combustion synthesis method using the above-mentioned metal aluminum has been confirmed to have a problem that it is obtained in a firmly fused block state depending on the production conditions even if a diluent is used to reduce the bulk density. Therefore, in order to use the obtained aluminum nitride as a raw material for a sintered body, pulverization is indispensable. As a result, due to the generation of a crushed surface that is easily oxidized due to pulverization, an oxide layer is formed on the surface of the aluminum nitride particles, which becomes a factor that increases the oxygen content of the aluminum nitride powder. When the aluminum nitride powder is calcined as a raw material, there is a problem that it is difficult to obtain an aluminum nitride sintered body having the required excellent thermal and electrical characteristics.
[0019] Solutions for solving problems
[0020] The present inventors have repeatedly conducted in-depth studies in view of the problems of the prior art and have found that, by using specified aluminum nitride particles as a diluent and carrying out a combustion synthesis reaction under specific conditions, the aluminum nitride obtained is in the form of a mass of loosely aggregated primary particles with a particle size of several μm. This can be processed into particles of an appropriate size by light crushing (hereinafter, this operation is also referred to as "crushing"), for example without using a crushing medium, thereby completely solving the above-mentioned problems and completing the present invention.
[0021] That is, the method for producing aluminum nitride powder of the present invention is a method for producing aluminum nitride by a combustion synthesis method using metal aluminum powder, characterized in that a mixed powder is ignited in a nitrogen atmosphere to be burned, wherein the mixed powder is obtained by mixing an aluminum nitride powder having an average primary particle size of less than 3 μm as a diluent in a ratio of 150 to 400 parts by mass relative to 100 parts by mass of the metal aluminum powder.
[0022] In the above-mentioned production method, the average particle size of the metal aluminum powder is preferably 1 μm or more and less than 10 μm.
[0023] It is further preferred that the bulk density of the mixed powder is between 0.6 and 0.9 g / cm 3 range.
[0024] It is preferred that the aluminum nitride mass obtained by combustion is crushed into a size having an average particle size exceeding the average primary particle size of the aluminum nitride particles constituting the mass and being 20 μm or less, and a part of the crushed mass is used as the diluent.
[0025] Furthermore, it is preferred that the mixed powder is filled in a layered manner to a bottom area of 0.3 m 2 The above flat box of heat-resistant material is ignited to make the metal aluminum powder burn.
[0026] It is preferable to form a heat insulating layer on the bottom surface of the flat box.
[0027] The aluminum nitride powder of the present invention is characterized in that it is formed of aluminum nitride primary particles with an average primary particle size of 3 μm or less and contains aggregated particles with a crush strength of 300 MPa or less, and the size of the aluminum nitride powder is an average particle size exceeding the above average primary particle size and being 20 μm or less.
[0028] The aluminum nitride powder preferably has a carbon concentration of 300 mass ppm or less.
[0029] These aluminum nitride powders can be obtained by the above-mentioned production method. In addition, the aluminum nitride powder of the present invention is preferably packed in a resin packaging bag.
[0030] Effects of the Invention
[0031] According to the present invention, aluminum nitride can be obtained in a bulk state, which can be easily finely divided by light pulverization (ie, crushing), which cannot be obtained by the existing combustion synthesis method.
[0032] Moreover, the aluminum nitride powder obtained by crushing the above-mentioned aluminum nitride block into an average particle size that exceeds the average primary particle size of the aluminum nitride particles constituting it and is less than 20μm is an aggregate of primary particles with an average primary particle size of less than 3μm. The above-mentioned aggregate has a small aggregation force (small crushing strength) and a small number of active surfaces generated by crushing. Therefore, it has the characteristic of extremely low oxygen concentration.
[0033] The aluminum nitride powder of the present invention formed in this aggregate state has less dusting and is easy to handle. When used as a raw material for a sintered body, even if it is used directly without being crushed, it can be easily loosened by shearing when mixed with an organic binder. Therefore, roasting with high processing efficiency and production efficiency can be carried out. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described.
[0035] Method for producing aluminum nitride powder
[0036] The metal aluminum powder used as the raw material itself can be a known product or a commercial product. In addition, there is no particular restriction on its preparation method, and a product obtained by any manufacturing method can be used. The purity of the metal aluminum powder is not particularly limited, but if the thermal conductivity of the product is taken into consideration, it is usually preferably 99.9% by mass or more (wherein the oxygen content is not included in the calculation of the purity).
[0037] The average particle size of the metal aluminum powder is usually expected to be greater than 1 μm and less than 10 μm, preferably greater than 1.5 and less than 10 μm. If a metal aluminum powder with a large average particle size is used, a large amount of aluminum nitride powder with a large particle size that is difficult to loosen may remain. If the average particle size is small, the workability is low and the metal is easily oxidized.
[0038] In addition, the amount of oxygen contained in the metal aluminum powder (oxygen content) can be appropriately set according to the use of the final product, reaction conditions, etc., and is generally set to about 0.05 to 1 mass%, and particularly preferably set to 0.1 to 0.6 mass%. When the above oxygen content is less than 0.05 mass%, there is a tendency for the metal aluminum powders to be easily fused during the reaction, and the nitrogen gas supply to the powder becomes insufficient, resulting in a concern that the nitriding rate is reduced. In addition, if the above oxygen content exceeds 1 mass%, the oxide film on the surface of the metal aluminum powder particles may hinder the nitriding reaction.
[0039] In the present invention, aluminum nitride powder is blended as a diluent together with the aforementioned metal aluminum powder.
[0040] The average primary particle size of the aluminum nitride powder is preferably 3 μm or less, preferably 2 μm or less. When the average primary particle size of the aluminum nitride powder used as a diluent is larger than the above range, the metal aluminum particles or the generated aluminum nitride particles will be significantly welded during the reaction, and as a result, the obtained aluminum nitride will become a solid block, and the purpose of the present invention cannot be achieved.
[0041] In the present invention, the aluminum nitride powder used as the diluent is not particularly limited in state as long as the average primary particle size is within the above range. For example, the aluminum nitride powder may be in a state of dispersed primary particles, in a state of aggregated particles of aggregated primary particles, or a mixture thereof.
[0042] Specifically, aluminum nitride powder obtained by reduction nitridation can be cited. The aluminum nitride powder obtained by reduction nitridation is usually present in a dispersed state of particles with an average primary particle size of about 1 μm, so it is preferred. In addition, it is also preferred to use a part of the aluminum nitride powder obtained by the method of the present invention as a diluent. As described later, the aluminum nitride powder can be obtained in the form of aggregated particles of primary particles with an average primary particle size of less than 3 μm, and can be used directly as a diluent.
[0043] In the most preferred embodiment of the present invention, aluminum nitride powder obtained by a reduction nitridation method is used at the start of the reaction, and then part of the aluminum nitride powder obtained by the production method of the present invention is used as a diluent.
[0044] The reaction can be controlled by the mixing ratio of the metal aluminum powder and the aluminum nitride powder. The ratio is preferably 150 to 400 parts by mass, preferably 200 to 350 parts by mass of the aluminum nitride powder relative to 100 parts by mass of the metal aluminum powder. If mixed at this ratio, combined with the above-mentioned specific average primary particle size, the reaction can be fully controlled, and easily crushable aluminum nitride blocks can be obtained, and the production efficiency can be improved.
[0045] In the present invention, as a method for mixing the metal aluminum powder and the aluminum nitride powder, a known mixing method can be adopted without particular limitation, and a mixing method using a ball mill, a V-type blender, a ribbon mixer, or the like is common.
[0046] Furthermore, the bulk density of the mixed powder can be appropriately set according to the particle size of the powder, reaction conditions, etc., and is preferably generally set to 0.6 to 0.9 g / cm 3 , preferably 0.7 to 0.9 g / cm 3 When it is within this range, nitrogen gas is sufficiently supplied to the mixed powder or combustion is sufficiently performed, unreacted metal aluminum is reduced, and easily breakable aluminum nitride blocks can be obtained.
[0047] In the production method of the present invention, in order to make the chain reaction of the metal aluminum powder proceed, a sufficient nitrogen source required for the reaction must be present on the powder surface of the reacting portion, and therefore, the nitrogen-containing atmosphere is preferably an atmosphere containing nitrogen gas at 1.0 to 10 atmospheres, preferably 1 to 8 atmospheres. As the nitrogen-containing atmosphere, nitrogen or ammonia or a non-oxidizing gas containing them can be used industrially.
[0048] In the manufacturing method of the present invention, as long as the above-mentioned mixed powder is used under the above-mentioned nitrogen atmosphere conditions, there are no particular restrictions on the conditions and methods of the combustion synthesis reaction itself. For example, in a pressurized reaction vessel with appropriately adjusted nitrogen pressure, by igniting a portion of the metal aluminum powder contained in a flat box-shaped container made of a heat-resistant material, the nitriding reaction can be carried out. In this case, in order to keep the nitrogen pressure constant or to prevent the nitrogen pressure from falling below a specified pressure, it is desirable to carry out the reaction while continuously resupplying nitrogen to the reaction vessel in the atmosphere. In addition, there is no particular restriction on the ignition method, and any method that can start the combustion synthesis reaction can be used, for example: a method of burying a resistor such as carbon in the metal aluminum powder and heating the resistor; a method of burying a known ignition agent in the metal aluminum powder and igniting the ignition agent; a method of irradiating the metal aluminum powder with an electron beam or a laser; etc.
[0049] A cooling device may also be provided near the reaction vessel to prevent the reaction temperature from rising excessively. The cooling device may be air cooling or water cooling.
[0050] In order to implement the present invention industrially, a preferred embodiment is to use a reaction vessel having a bottom area of 0.3 m2 for the mixed powder. 2 A container with an area of more than 1000 square meters is used, specifically, a flat box made of a heat-resistant material such as carbon. In addition, the flat boxes are preferably stacked in layers to ensure a supply space for nitrogen. The mixed powder is filled into the flat box and ignited to cause the metal aluminum powder to undergo a combustion reaction.
[0051] In addition, the mixed powder filled in the flat box preferably forms a powder layer with a thickness of 10 to 80 mm. If the thickness of the mixed powder is within this range, the heat release is sufficiently higher than the heat dissipation, so that the combustion temperature does not decrease and the nitriding rate does not decrease. In addition, since the nitrogen supplied from the surface of the powder layer fully reaches the bottom of the powder layer, the nitriding rate at the bottom can be increased.
[0052] When the method of the present invention is implemented industrially, it is desirable to use a reaction vessel having a bottom area of 0.3 m 2 Above, preferably 0.5 to 3 m 2When using such a large-area reaction container, it is preferred to form a heat insulating layer on the bottom surface to prevent heat loss from the surrounding walls of the container, especially from the bottom surface, and to effectively transfer the reaction heat in the aforementioned mixed powder.
[0053] The heat-insulating layer may be made of any material as long as it is a material that does not participate in the reaction. Specific examples thereof include aluminum nitride and boron nitride, and aluminum nitride is particularly preferred.
[0054] As the form of the heat insulating layer, there can be cited: a form in which a powder coating layer exists in a powder form, a form in which it is formed into a plate form and is provided on the bottom surface portion, etc. It should be noted that the heat insulating layer formed into a plate form is not limited to a dense plate-like body, and a porous plate or a perforated plate can also be used. It should be noted that in the case of forming the heat insulating layer in a powder form, if the aluminum nitride powder obtained by the method of the present invention is used, it is preferred that it does not become an impurity even if it is mixed into the product. In addition, the heat insulating layer formed into a plate form can also exist on the side of the reaction container. Furthermore, in the case of using aluminum nitride powder, it is also a preferred form to form the heat insulating layer by making it exist on the surface layer of the mixed powder filled in the reaction container.
[0055] The appropriate thickness of the heat insulating layer is about 5 to 10 mm.
[0056] The aluminum nitride obtained by the present invention is recovered in the form of flocculent masses, but since the aggregates are weak, the aluminum nitride powder can be easily obtained by crushing.
[0057] The crushing method is not particularly limited, but a crushing method using a medium such as a ball mill, a vibration mill, or a pulverizer can be used. However, since the aggregation is not strong, a crushing method without using a medium is preferably used. Specifically, a method using a pulverizing device such as a jet mill, a mass colloder, or a vibration mill without using balls can be cited.
[0058] The degree of the above-mentioned crushing is not particularly limited, but the aluminum nitride block obtained by the reaction is preferably crushed into a size having an average particle size exceeding the average primary particle size of the aluminum nitride particles constituting the aluminum nitride block and being 20 μm or less, preferably having an average particle size of 4 to 20 μm, and more preferably 5 to 15 μm. That is, by crushing into the above-mentioned size, an aluminum nitride powder having no dusting and excellent handleability is obtained.
[0059] Furthermore, as described later, if the obtained aluminum nitride powder has a primary particle size of 3 μm or less, it can be suitably used as a raw material for sintering.
[0060] In addition, a part of the aluminum nitride powder having the above primary particle size can be used as a diluent in the production method of the present invention without any problem.
[0061] According to the manufacturing method of the present invention, since a combustion synthesis reaction is utilized, no external heating (forced heating) is required, and by using a prescribed diluent, aggregation is weak, and high-quality aluminum nitride can be manufactured by a simple crushing process. Based on these effects, compared with the existing manufacturing method, significant cost reduction and high efficiency can be achieved.
[0062] As described above, the method for producing aluminum nitride of the present invention is suitable for production on an industrial scale and can provide aluminum nitride at a low price.
[0063] [Aluminum nitride powder]
[0064] The average primary particle size of the aluminum nitride powder obtained by the aforementioned method of the present invention is as small as less than 3 μm, and is obtained by moderately crushing the aluminum nitride blocks obtained as weak aggregates. Therefore, it is possible to maintain the same average primary particle size as that of the aluminum nitride powder obtained by the existing reduction nitriding method, and to obtain aggregated particles that maintain a moderate aggregation state.
[0065] Therefore, the aluminum nitride powder has high sinterability due to the primary particle size, and can be handled as aggregated particles aggregated with appropriate strength, with less dusting, which is also beneficial to the working environment.
[0066] That is, according to the present invention, there is provided an aluminum nitride powder comprising aggregated particles of aluminum nitride primary particles having an average primary particle size of less than 3 μm, wherein the size of the aggregated particles is an average particle size exceeding the average primary particle size and less than 20 μm, preferably 4 to 20 μm, and further preferably 5 to 15 μm, and the crushing strength is less than 300 MPa.
[0067] The aluminum nitride powder of the present invention preferably has a carbon concentration of 300 mass ppm or less, more preferably 200 mass ppm or less.
[0068] In addition, the oxygen content of the aluminum nitride powder of the present invention is 1.3 mass % or less, preferably 1.0 mass % or less. In the present invention, the average primary particle size is measured using a scanning electron microscope, and the average particle size of aggregated particles is measured using a particle size distribution meter (MT3000IIEX manufactured by Micro Track Bell Co., Ltd.).
[0069] By applying the aggregated particles of the aluminum nitride primary particles of the present invention to a sintered body, an aluminum nitride powder that is easy to handle and has good dispersibility in a solvent is obtained. In addition, in the aluminum nitride powder, the aggregated particles are weakly aggregated, and since the crushing strength is weak, there are few new surfaces generated by particle disintegration, and the oxygen concentration of the powder after being dispersed in the solvent is low, so the thermal conductivity of the sintered body is high.
[0070] Such aluminum nitride powder can be produced, for example, by the above-mentioned production method.
[0071] Since it is produced by combustion synthesis reaction, the carbon concentration in the powder is inherently low. In addition, even if aluminum nitride powder produced by reduction nitridation is used as a diluent at startup, the carbon concentration decreases gradually as the aluminum nitride produced is recycled as a diluent. Moreover, the whiteness of the aluminum nitride powder of the present invention with such low carbon content becomes extremely high.
[0072] Moreover, since the aluminum nitride powder of the present invention can be shipped in the form of aggregates having the aforementioned average particle size, the powder will not scatter when mixed with a resin or a solvent, thereby improving operability. Furthermore, since the crushing strength is low, the powder is easily loosened and dispersed.
[0073] Therefore, the aluminum nitride powder of the present invention can be filled into a resin packaging bag such as a drum can, a PET can, a bulk bag, or a paper bag and transported. The present invention can also provide such a packaging body.
[0074] Example
[0075] Hereinafter, although an Example is shown and the characteristic of this invention is demonstrated concretely, this invention is not limited to these Examples at all.
[0076] [Example 1]
[0077] A metal aluminum powder having an average particle size of 8 μm, an oxygen content of 0.05 mass%, and an impurity content of 0.1 mass% other than oxygen was mixed with an aluminum nitride powder having an average primary particle size of 1 μm, an oxygen content of 0.8 mass%, and an impurity content of 0.1 mass% other than oxygen produced by a reduction nitridation method in a ratio of 350 parts by mass to 100 parts by mass of the metal aluminum powder to prepare a mixed powder, and the mixed powder was filled to a flat bottom area of 0.4 m 2 The aluminum nitride block was crushed by a vibration mill without using balls to obtain D 50 The aluminum nitride powder had an average primary particle size of 8.2 μm, an average primary particle size of 1 μm, and a crushing strength of 250 MPa. The oxygen concentration of the obtained aluminum nitride powder was 0.7 mass %.
[0078] The aluminum nitride powder obtained by the above method was used as a diluent, and the combustion synthesis reaction was repeated 5 times in the same manner as above, and the aluminum nitride powder was crushed in the same manner. As a result, the average particle size, average primary particle size, crushing strength, and oxygen concentration were substantially the same. In addition, the aluminum nitride powder obtained by recycling the generated aluminum nitride powder as a diluent 5 times had a carbon concentration reduced to 180 ppm.
[0079] 5 parts by mass of yttrium oxide powder and 10 parts by mass of a binder were added to 100 parts by mass of the aluminum nitride powder, and a solvent was added and mixed, and the obtained slurry was formed into a sheet.
[0080] The sheet compact was cut into a predetermined size and sintered at 1800°C to produce a sintered body. The density and thermal conductivity of the obtained sintered body were measured and found to be 3.321 g / cm 3 , 181W / mk.
[0081] [Example 2]
[0082] In Example 1, a jet mill was used instead of a vibration mill to crush the powder after the nitriding reaction. The powder was crushed in the same manner to obtain aluminum nitride powder. In addition, the obtained aluminum nitride powder was formed into a sheet by the same method as in Example 1, and then a sintered body was prepared and evaluated. The obtained powder was D 50 The aluminum nitride powder has an average primary particle size of 6.4 μm, an average primary particle size of 1 μm, an oxygen concentration of 0.8 mass %, and a crushing strength of 240 MPa. Furthermore, when the density and thermal conductivity of the sintered body were measured, it was 3.34 g / cm 3 , 180W / mk.
[0083] [Example 3]
[0084] In Example 2, the crushing energy of the jet mill after the nitriding reaction was reduced, and the crushing was carried out in the same manner to obtain aluminum nitride powder. The obtained aluminum nitride powder was formed into a sheet by the same method as in Example 1, and then a sintered body was prepared and evaluated. The obtained powder was D 50 The aluminum nitride powder has an average primary particle size of 10.4 μm, an average primary particle size of 1 μm, an oxygen concentration of 0.8 mass %, and a crushing strength of 240 MPa. Furthermore, when the density and thermal conductivity of the sintered body were measured, it was 3.34 g / cm 3 , 179W / mk.
[0085] [Comparative Example 1]
[0086] In Example 1, the aluminum nitride powder for dilution was mixed in a ratio of 100 parts by mass to 100 parts by mass of the metal aluminum powder to prepare a mixed powder. The aluminum nitride powder obtained was formed into a sheet by the same method as in Example 1, and then a sintered body was prepared and evaluated. The obtained powder was D 50 The aluminum nitride powder has an average primary particle size of 26 μm, an average primary particle size of 5 μm, an oxygen concentration of 0.6 mass %, and a crushing strength of 340 MPa. Furthermore, when the density and thermal conductivity of the sintered body were measured, it was 2.79 g / cm 3 , 95W / mk.
[0087] The nitriding reaction was similarly attempted using the aluminum nitride powder obtained above as a diluent, but the flame was not transferred from the ignition agent and the reaction did not proceed.
[0088] [Comparative Example 2]
[0089] In Example 1, a powder having an average particle size of 15 μm was used as aluminum nitride powder for dilution, and was mixed in a ratio of 300 parts by mass to 100 parts by mass of metallic aluminum powder to prepare a mixed powder. Except for this, the nitriding reaction was carried out in the same manner, but the flame was not transferred from the ignition agent and the reaction did not proceed.
Claims
1. A method for producing aluminum nitride powder, which is a method for producing aluminum nitride by a combustion synthesis method using metallic aluminum powder, characterized in that: Aluminum nitride powder having an average primary particle size of 3 μm or less is used as a diluent, and the diluent is mixed in a ratio of more than 200 parts by mass and less than 400 parts by mass relative to 100 parts by mass of the metal aluminum powder, and the bulk density is adjusted to 0.6 to 0.9 g / cm 3 The mixed powder in the range of is ignited in a nitrogen atmosphere to be burned to obtain an aluminum nitride block, and the aluminum nitride block obtained by the above manufacturing method is crushed into particles with an average particle size of 4 to 20 μm to obtain an aluminum nitride powder with an average primary particle size of less than 3 μm and containing aggregated particles with a crushing strength of less than 300 MPa, and the aluminum nitride powder is recycled as the diluent.
2. The method for producing aluminum nitride powder according to claim 1, wherein: The average particle size of the metal aluminum powder is 1 μm or more and less than 10 μm.
3. The method for producing aluminum nitride powder according to any one of claims 1 or 2, wherein: The aluminum nitride mass obtained by combustion is crushed into a size that exceeds the average primary particle size of the aluminum nitride particles constituting the mass and is 20 μm or less, and a portion of the crushed mass is used as the diluent.
4. The method for producing aluminum nitride powder according to claim 1 or 2, wherein: The mixed powder is filled in layers to a bottom area of 0.3 m 2 The above flat box of heat-resistant material is ignited to make the metal aluminum powder burn.
5. The method for producing aluminum nitride powder according to claim 4, wherein: A heat insulating layer is formed on the bottom surface of the flat box.
6. An aluminum nitride powder, characterized in that: It is formed of aluminum nitride primary particles with an average primary particle size of 3 μm or less and includes aggregated particles with a crushing strength of 300 MPa or less. The size of the aluminum nitride powder is an average particle size of 4 to 20 μm and exceeds the average primary particle size of the aluminum nitride particles.
7. The aluminum nitride powder according to claim 6, wherein The carbon concentration is 300 mass ppm or less. 8 . A packaged body, wherein the aluminum nitride powder according to claim 6 or 7 is filled in a resin packaging bag.
Citation Information
Patent Citations
Production of silicon nitride
JP1995081909A
Production of aluminum nitride
JP2000016805A
Production of aluminum nitride powder
JP1995309611A
Aluminum nitride, aluminum nitride containing solid solutions and aluminum nitride composites prepared by combustion synthesis
US5649278A